Rewiews - Francesca Giglio (TECHNE - Journal of Technology for Architecture and Environment, 2020)
Time and Architecture. The aspects that involve its dichotomous and synchronic relationship (De Fusco, 2019)1, make it a constantly present topic in the architectural debate, intrinsic to any disciplinary aspect. The multiplicity of meanings that the relationship between the two terms can trigger, continuously widens its field of investigation and its interpretation. On the interpretation of Time, Vittorio Gregotti, in the last period of his life, wanted to leave a further testimony. He read and recounted it as past, present and future as the structural material of the design in relation to space, place and use. With regret for not having been able to enrich the Reviews section with “Tempo e Progetto”2, we want to remember him with his words: «The architectural design is the ability to produce, in the present and in the future, fragments of new truths, which never forget the critical territory of the past, the history of its discipline and its context» (Gregotti, 2020). A concept that is more actual than ever, confronting an epochal period of particular criticality, transition, in which all professional categories are called to give a contribution to tell a Time that is changing, also and above all, in relation to Architecture. Gaetano Pesce’s exhibition, “Il rumore del tempo” (The noise of time) in 2005 at the Milan Triennale, already recounted the omens, with a holistic vision between Design, Music, Art, Architecture, to stage the absolute subjectivity of the relationship with Time and therefore its inevitable relativity. Taking up the words of Osip Mandel’štam3 (2014) “time makes noise when we tell an era” as expressed by dichotomies such as Temporariness/Durability, Reversibility/Permanence that represent and typify our Time – perhaps critical for Architecture – in the new paradigms of interpretation of space, performance, languages, building techniques. The Reviews section proposes three texts selected according to a method that refers to the topics related to the relationship between Time and Architecture: the first, with regard to the disciplinary field of Technology of Architecture, the second more general but referable to the Architecture Area, the third as an essay on the Theme. Three research experiences with different approaches, which see in the relationship with Time: the Temporariness as a new constructive paradigm, the unfinished as a provocative architectural style and the Physics as the main road to study its theoretical principles. The first text – “Il progetto del temporaneo. Tra ricerca e formazione: dispositivi per l’arte, la cultura, il patrimonio”, by Antonio Capestro and Leonardo Zaffi (2019), Didapress, Florence – is reviewed by Danila Longo4. The text addresses the theme of Temporariness through four research sections conducted by the two authors at the Department of Architecture in Florence. The text addresses the theme of Temporariness through four research sections conducted by the two authors at the Department of Architecture in Florence. Temporary architecture is read and proposed as a work programmed to die, which exasperates the constituent elements, accelerates the design and building processes and condenses the cultures of the design. In this context, D. Longo traces the salient traits on the relationship between ephemeral spaces of exhibition design and historical Florentine contexts, on the constructive dimension of temporary architecture, on design experiments and experiences of self-construction and on the final photographic sequence of site-specific architecture, with critical analysis and method with respect to the articulation and concatenation of the themes addressed. The concept of Temporariness, although with a different latent meaning, finds its derivation also in that phenomenon that is rampant in Italy – mainly in the South of Italy – which is the Incompletion. The project of the Unfinished and its relationship with the passing of time is told and read as an architectural style, bordering on the provocative, through critical writings and photographs in “Incompiuto: La nascita di uno Stile”, Humboldt (2018), edited by Alterazioni Video and Fosbury Architecture5 , reviewed by Matteo Gambaro6. The phenomenon of contemporary ruins described and denounced in the text in quantitative and qualitative terms, is treated by M. Gambaro with a spirit that goes beyond the risk of a trivial interpretation. By reporting Marco Biraghi’s words on the unfinished as «typically Italian modus operandi, a de facto style, a malgré soi style», he highlights both the rigorous aspects through which the research activity on the subject has been tackled and the innovative inputs that the subject proposes. The review interweaves in a balanced way the photographic contributions together with the critical essays, underlining also the role of the heterogeneous communicative modalities that the text proposes. The description of the passage and transformation of Time – in its results on unfinished architecture – is translated into scientific and theoretical aspects in the third text “L’ordine del tempo”, Adelphi (2017) by Carlo Rovelli, reviewed by Alessandra Zanelli7. The text is divided into three parts: the first defines time as a complex collection of layers, the second concerns what we know today about time, the third identifies the challenge we can take on for the future. A. Zanelli describes every nuance of the text with incisiveness, telling it as a journey through time and space that forces us to come to terms with three essential aspects of our nature as observers of the cosmos: incessant curiosity, the need to find an order to what we see or think we understand, the desire to connect events through memory. As a corollary of these theories, Rovelli’s studies on loop quantum gravity equations show that the variable Time no longer exists, identifying new concepts of spatiality. The theme of Time will never be exhausted in its contents and its extensions; also present in the candidacy of Parma as Italian Capital of Culture 2020 (extended to 2021) as an instrument of regeneration through culture, of the ability to rhythm the life of cities, and to break down historical and social barriers through processes of sharing and growth8, the relationship between Time and Architecture, will continue to be constantly nourished also for and in the idea of the project «which must reveal itself [...], as a long bridge between the critical judgment on the present, the consciousness of the past, and a possible necessary hypothesis of the future» (Gregotti, 2020). NOTES 1 De Fusco, R. (2019), Linguistica, Semiotica e Architettura, Altralinea, Firenze. 2 Gregotti, V. (2020), Tempo e progetto, Skira. 3 Mandel’štam, O. (2014), Il rumore del tempo e altri scritti, Adelphi. 4 Danila Longo is Associate Professor of Technology of Architecture at the Department of Architecture of Alma Mater Studiorum, University of Bologna. 5 Alterazioni Video and Fosbury Architecture are two collectives of artists and architects with Milanese origins and international branches in Europe and the USA. 6 Matteo Gambaro is Associate Professor of Technology of Architecture at the Department of Architecture Construction Engineering and Built Environment (ABC) Politecnico of Milano. 7 Alessandra Zanelli is Full Professor of Technology of Architecture at the Department of Architecture Construction Engineering and Built Environment (ABC) Politecnico of Milano. 8 Manifesto, culture beats Time, Parma Capitale italiana della cultura 2020.